The Development of Schools in the Mandar Afdeling During the Colonial Period, 1911–1942 - Muh. Ilham Noer Hamsah; Arif Akhyat (UIN Imam Bonjol Padang, 2026)
This article examines the development of schools in the Mandar Afdeling during the Dutch East Indies colonial period from 1911 to 1942 and their impact on the social life of local society. The study aims to analyze the background of the introduction of formal education, the growth patterns of schools managed by the colonial government, missionary (zending) institutions, and nationalist organizations, as well as their implications for changes in social structure and local power relations. The research employs the historical method, encompassing heuristics, source criticism, interpretation, and historiography, and is supported by a social history approach. The findings indicate that colonial education in Mandar did not merely function as a means of intellectual advancement, but also served as an instrument for bureaucratic formation and social control. Schools contributed to the emergence of an educated bureaucratic elite and facilitated a theological shift from local belief systems toward Christianity in inland areas through zending schools. Meanwhile, schools established by nationalist organizations played a role in fostering social awareness and national consciousness. Thus, education became a crucial factor in the social change of Mandar society in the early twentieth century.